Aspirin Use and Mortality in Women With Ovarian Cancer: A Meta-Analysis - Man, Xiaxia; Wang, Baogang; Tan, Yuying; Yang, Xiaolin; Zhang, Songling (Frontiers in Oncology, 2021)
Background: Aspirin use has been suggested to reduce the incidence of ovarian cancer (OC) in women. However, previous studies regarding the association between aspirin use and mortality in women with OC showed inconsistent results. We aimed to evaluate the association between aspirin use and mortality in women with OC in a meta-analysis. Methods: Relevant cohort studies were obtained via search of PubMed, Cochrane’s Library, and Embase databases from inception to May 3, 2020. A random-effect model, which incorporates the potential heterogeneity among the included studies, was used to pool the results. Predefined stratified analyses were applied to evaluate the potential study characteristics on the outcome, including the timing of aspirin use, dose of aspirin, age of the women, and the clinical stages of the cancer. Sensitivity analysis by omitting one study at a time was used to assess the stability of the results. Results: Six cohort studies including 17,981 women with OC were included. Pooled results showed that aspirin use was not statistical significantly associated with mortality in these patients (adjusted risk ratio [RR]: 0.85, 95% confidence interval [CI]: 0.70 to 1.02, p = 0.08; I2 = 69%). The results were similar for OC-specific mortality (RR: 0.85, 95% CI: 0.57 to 1.26, p = 0.41) and all-cause mortality (RR: 0.78, 95% CI: 0.55 to 1.11, p = 0.17). Stratified analyses suggested that aspirin use was not statistical significantly associated with mortality risk in OC regardless the timing of aspirin use, dose of aspirin, age of the women, or the clinical stages of the cancer. Funnel plots suggested potential risk of publication bias (p all > 0.05). However, further “trim-and-fill” analysis incorporating hypothesized unpolished studies to achieve symmetrical funnel plots showed similar results of the meta-analysis (RR: 0.91, 95% CI: 0.74 to 1.13, p = 0.39). Conclusions: Current evidence from observational studies indicated that aspirin use was not statistical significantly associated with mortality in women with OC.